1987
DOI: 10.1136/vr.120.21.500
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of experimental haemorrhagic septicaemia with a live vaccine

Abstract: Pasteurella multocida serotype B:3,4 isolated from a fallow deer in England was used as a vaccine to prevent haemorrhagic septicaemia. The deer strain was less virulent for calves than typical serotype B:2 of haemorrhagic septicaemia strains. It elicited antibodies in cattle that protected mice against serotype B:2 infection. The live deer vaccine containing 2 X 10(7) viable organisms per dose was used to immunise calves. Six months after vaccination, five of six calves were protected against serotype B:2 chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 0 publications
0
17
1
Order By: Relevance
“…However, the mechanism of attenuation for all of these strains is unknown and the vaccines retain a degree of virulence under experimental conditions (Hopkins and Olson 1997 ) and have occasionally caused disease outbreaks in the fi eld (Hopkins et al 1998 ). Live vaccines for HS have been derived from fi eld isolates, such as the serotype B:3,4 strain isolated from deer (Myint et al 1987 ). Again, while demonstrating a good degree of effi cacy, the basis for the observed attenuation is unknown and these vaccines have not gained widespread usage (Verma and Jaiswal 1998 ).…”
Section: Live Vaccinesmentioning
confidence: 99%
“…However, the mechanism of attenuation for all of these strains is unknown and the vaccines retain a degree of virulence under experimental conditions (Hopkins and Olson 1997 ) and have occasionally caused disease outbreaks in the fi eld (Hopkins et al 1998 ). Live vaccines for HS have been derived from fi eld isolates, such as the serotype B:3,4 strain isolated from deer (Myint et al 1987 ). Again, while demonstrating a good degree of effi cacy, the basis for the observed attenuation is unknown and these vaccines have not gained widespread usage (Verma and Jaiswal 1998 ).…”
Section: Live Vaccinesmentioning
confidence: 99%
“…The vaccine protected cattle vaccinated subcutaneously against a serotype B:2 challenge and conferred immunity against HS for a year [15] . Cross-protection by P. multocida serotype B:3,4 in a live intranasal vaccine against a subcutaneous challenge with serotype B:2 has been confirmed in Myanmar [16] . This study revealed outer membrane proteins (OMPs) as common immunogenic components (MW 39.0, 33.5, 31.0 kDa) of P. multocida serotypes B:3,4 and B:2, rendering B:3,4 a successful candidate for use as a live vaccine against haemorhhagic septicaemia.…”
Section: Introductionmentioning
confidence: 85%
“…5). Based on quantitative analysis of gel bands, Tomer et al [16] also reported three polypeptides MW of 31, 33 and 37 kDa, with 37 kDa fraction being highly antigenic. Whereas other study reported polypeptides of 44, 37 and 30 kDa being major immunogens among ten polypeptide bands of 25 to 88 kDa in a study on outer membrane protein from P. multocida serotype B:2 [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Immunity generated in HS is serotype-specific therefore selection of vaccine candidates depend upon circulating serotypes in that geographical regions. Various strategies have been used to develop HS vaccines such as killed vaccines (bacterins), live-attenuated, cellular vaccines, and genetically-engineered vaccines (Myint et al, 1987;Verma and Jaiswal, 1998;Hodgson et al, 2005). But killed vaccines are used commonly for the vaccination against HS.…”
Section: Hemorrhagic Septicemiamentioning
confidence: 99%